Preventing Digital Sexual Harassment: Strategies for Improving Digital Literacy An Islamic Education Perspective: Mencegah Pelecehan Seksual Digital: Strategi Meningkatkan Literasi Digital dalam Perspektif Pendidikan Islam - eka rizky bastian; Muhammad Thohir (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Digital harassment is becoming increasingly widespread and has become a serious problem in the digital era, including among society, especially Indonesian society. harassment itself definitely has an impact on the victim, and it definitely has a bad and negative impact, both physically and mentally. Islamic education plays an important role which is expected to prevent digital harassment by instilling moral and ethical values ​​in society. In this research we aim to explain strategies for increasing digital literacy from an Islamic education perspective as a form of preventing digital harassment. Using qualitative methods and a literature study approach. We dive into various sources to provide various data, such as books, scientific journals, and online articles. The data analysis technique uses thematic analysis and content analysis. The end of this research shows that there are several strategies to increase digital literacy as a form of preventing digital harassment in accordance with Islamic education. First, instilling Islamic moral and ethical values ​​in every human being. Second, developing knowledge and skills about information and communication technology. Third, developing the character of people with good character and high morals. This strategy must be implemented effectively in the Islamic education process in schools as well as in the general public in order to create a generation that is responsible and has noble character in the digital era.